Efikasi herbisida butil sihalofop terhadap gulma dominan serta implikasinya terhadap pertumbuhan dan hasil padi sawah - Fadhli Hermawan; Dedi Widayat; Miftah Dieni Sukmasari; Umar Dani (Fakultas Pertanian Universitas Majalengka, 2026)
Weed management is a critical factor in improving rice productivity because weeds compete with rice plants for light, water, nutrients, and growing space. This study aimed to evaluate the effectiveness of Butyl Cyhalofop 400 g L⁻¹ herbicide on rice growth, phytotoxicity, and yield performance. The experiment was arranged in a Randomized Complete Block Design consisting of six treatments: Butyl Cyhalofop 400 g L⁻¹ applied at rates of 0.75, 1.0, 1.25, and 1.50 L ha⁻¹, an untreated control, and manual weeding. Observed variables included rice phytotoxicity, plant height, tiller number, productive tillers, harvested dry grain yield (HDG), and milled dry grain yield (MDG). Data were analyzed using analysis of variance (ANOVA), followed by Duncan’s Multiple Range Test at the 5% significance level. The results showed that the application of Butyl Cyhalofop 400 g L⁻¹ caused no phytotoxic effects on rice plants up to three weeks after application. The herbicide had no significant effect on the number of tillers but significantly affected plant height, productive tillers, HDG, and MDG. The application rate of 1.50 L ha⁻¹ produced the highest number of productive tillers (17.50 tillers hill⁻¹), as well as the highest HDG and MDG values of 2.42 and 1.80 kg plot⁻¹, respectively. These results were comparable to those obtained under manual weeding for several measured parameters. Overall, Butyl Cyhalofop 400 g L⁻¹ maintained normal rice growth and improved yield components compared with the untreated control. Therefore, Butyl Cyhalofop 400 g L⁻¹, particularly at the rate of 1.50 L ha⁻¹, can be considered an effective and selective herbicide for weed management in rice cultivation.